Studies in engineering education - Virginia Polytechnic Institute (Virginia Tech Publishing, 2020)
"SEE is an international, open-access, peer reviewed journal that provides a venue for high-quality research conducted in all settings and contexts relevant to engineering education, with an emphasis on contextually rich reflective discussions of issues and approaches important to engineering education researchers and practitioners."
Keywords: Engineering : Study and teaching : Research : Periodicals